An Investigation of ZZ/ZW and XX/XY Sex Determination Systems in North African Catfish (Clarias gariepinus, Burchell, 1822) - Nguyen, Dung Ho My; Panthum, Thitipong; Ponjarat, Jatupong; Laopichienpong, Nararat; Kraichak, Ekaphan; Singchat, Worapong; Ahmad, Syed Farhan; Muangmai, Narongrit; Peyachoknagul, Surin; Na-Nakorn, Uthairat; Srikulnath, Kornsorn (Frontiers in Genetics, 2021)
Sex-specific loci offer powerful information for identifying sex determination systems. They offer a molecular biotechnological approach for producing all‐male or all-female fish for commercial breeding. The North African catfish (Clarias gariepinus, Burchell 1822) has been widely adopted for aquaculture, because its superior growth and disease resistance render the species suitable for hybridization with other catfish, to improve the productivity and quality of fish meat. North African catfish have either a ZZ/ZW or XX/XY sex determination system. Here, we investigate and characterize these systems using high-throughput genome complexity reduction sequencing as Diversity Arrays Technology. This approach was effective for identifying moderately sex-linked loci with both single-nucleotide polymorphisms (SNPs) and restriction fragment presence/absence (PA) markers in 30 phenotypic sex assignments of North African catfish. In total, 41 moderately male-linked loci met the criteria of moderately sex-linked loci (70:30, male:female; 80:20, male:female). By contrast, only 25 female-linked loci were detected from moderately sex-linked loci, and no perfectly male- or female-specific sex-linked loci were observed. Several moderately male-linked loci were partially homologous to some classes of transposable elements and functional genes. Our data showed that the male heterogametic XX/XY sex determination system should co-exist with the ZZ/ZW system in North African catfish and suggests that the region of suppressed recombination on Y might be highly cryptic. In addition, the ZZ/ZW type of North African catfish in a previous report was shown to exhibit heteromorphic sex chromosomes, whereas the two groups of North African catfish had different sex determination systems. Thus, turnover of sex chromosome systems might have occurred in ancestral homomorphic sex chromosomes. The XX/XY group has been introduced into Thailand for commercial breeding. This approach using moderately sex-linked loci provides a solid baseline for revealing sex determination mechanisms and identify potential sex determination regions in catfish, allowing further investigation of genetic improvements in breeding programs.